The warden's daughter - Spinelli, Jerry (New York : Alfred A. Knopf, 2017)
Living with her warden father in an apartment above a 1950s prison, Cammie O'Reilly struggles to come to terms with the loss of her mother, who died saving her from harm when she was a baby, and interacts with some of the reformed inmates.
"This is a Borzoi book"--Title page verso.
Accelerated Reader AR
A Junior Library Guild selection (JLG.)
Keywords: Teenage girls -- Juvenile fiction; Motherless families -- Juvenile fiction; Grief -- Juvenile fiction; Prisons -- Juvenile fiction; Prisoners -- Juvenile fiction; Teenage girls -- Fiction; Motherless families -- Fiction; Grief -- Fiction; Prisons -- Fiction; Prisoners -- Fiction; Teenage girls -- Juvenile Fiction; Prisons -- Juvenile fiction